Volume 4: Heat Transfer, Parts a and B 2012
DOI: 10.1115/gt2012-68513
|View full text |Cite
|
Sign up to set email alerts
|

Shear Layer Flame Stabilization Sensitivities in a Swirling Flow

Abstract: A variety of different flame configurations and heat release distributions can exist in high swirl, annular flows. Each of these different configurations, in turn, has different thermoacoustic sensitivities and influences on combustor emissions, nozzle durability, and liner heating. These different configurations arise because at least three flame stabilization locations are present, associated with the inner and outer shear layers of the annulus, and the stagnation point of the vortex breakdown region. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Schefer et al reported the dependency of flame macrostructures on fuel composition through hydrogen addition to a premixed air-methane mixture [11]. Chterev et al explored the effect of equivalence ratio and preheat temperature as well as geometrical features like the swirl number and the centerbody design on the different mean flame configurations [12,13]. The dependency of flame macrostructures on the Reynolds number has been also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Schefer et al reported the dependency of flame macrostructures on fuel composition through hydrogen addition to a premixed air-methane mixture [11]. Chterev et al explored the effect of equivalence ratio and preheat temperature as well as geometrical features like the swirl number and the centerbody design on the different mean flame configurations [12,13]. The dependency of flame macrostructures on the Reynolds number has been also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Combustor Design The experimental facility is was discussed in Ref. [36] and can be divided into a reactant supply system, flow preconditioning and fuel/air mixing, premixer, combustor, and exhaust sections. Upon entering the premixer section the outer and inner diameter of the test section are smoothly transitioned to the desired dimensions of 62 mm for the outer diameter and 36 mm for the inner or centerbody diameter.…”
Section: Methodsmentioning
confidence: 99%
“…The second feature of note is the decreased jet spread angle as a result of the hot products escaping from the OSL stabilized flame. As discussed previously [36], the transition points between these different configurations were characterized as a function of fuel/air ratio, preheat temperature, bulkhead temperature, and center body temperature. Figure 17 shows a typical flame configuration run, showing the OSL stabilization and blowoff lines.…”
Section: Flame Shape IIImentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers reported the existence of different flame shapes in swirl-stabilized combustion. These have been previously documented as function of fuel composition [7][8][9], equivalence ratio and preheat temperature [5,10] and Reynolds number [11], swirl number [12] as well as centerbody geometry [4]. Most of these studies reported the following flames although named differently: a columnar flame (I); a bubble-columnar flame (II); a single conical flame with a flame stabilized along the ISL (flame III); and a double conical flame with an additional continuous flame front stabilized in the ORZ and/or along the OSL (flame IV).…”
Section: Introductionmentioning
confidence: 99%